Genetic variation of pharmacogenes - Phuong Nhung, Vu; Dang Ton, Nguyen; Van Hai, Nong; Hai Ha, Nguyen (Vietnam Journal of Biotechnology, 2020)
Patient specific response against a particular drug could be affected by various factors, in which genetic factors are the most crucial contributor. The genetic variability in pharmacogenes might result in variable drug response of individuals, which in turn can lead to unexpected treatment outcomes or even adverse drug reactions. The pharmacogenes include of genes that encode for several proteins which divided into 3 main functional categories: drug metabolizing enzymes, drug transporters and receptor-drug targets. Genetic variants of genes coding for drug metabolizing enzymes phase I (CYP450), phase II (GSTs, UGT, TPMT) as well as drug transporters (ABC, SLCO) of numerous populations in global have been extensively studied. Among these, SNPs are the major contributor behind variants of pharmacogenes along with copy number variants. Furthermore, the clinical impact on drug response of common variants belonging to several important pharmacogenes has been well understood. On the other hand, information on the variant spectrum of genes encoding for receptor-drug targets as well as their physiological effects have remained limited. In recent years, along with computational methods, next generation sequencing technologies had been developed tremendously. These high throughput methods had greatly promoted the field of pharmacogenetic research through providing ability to detect novel and rare genetic variants. The data on genetic variants of pharmacogenes would be valuable for determining the responder and non-responder to medication during treatment. These are also significant basis which play a vital role in development of the field of optimizing drug dose for individuals and personalized medicine in the future.